IBLI M-learning app - Tsegaye, Tariku; Taye, Masresha; Gobu, Wako; Galgallo, Diba; Banerjee, Rupsha R. (International Livestock Research Institute, 2020)
Learning IBLI is an interactive multilingual (currently supporting Afan Orommo and Swahili) android application that provides assessment and video tutorial on Index Based Livestock Insurance. It contains Pre, Post and Post-Post assessment on IBLI. Between Pre and Post assessment, video tutorial module containing 7 courses with in-video multiple choice continuous assessment quizzes.